Analisis Biomekanika Gerak Anggota Tubuh Atas pada Jump Servis dan Spike dalam Permainan Bola Voli - Runesi, Salmon; Louk, Michael Johannes Hadiwijaya; Fufu, Ronal Dwi Ardian; Siagian, Fera Ratna Dewi; Neolaka, Erwin Sarnoto; Huwae, Joppi (Jurnal Porkes, 2025)
This research was conducted in March–May 2025 at Nusa Cendana University (UNDANA), Kupang, with the aim of analyzing the biomechanics of upper limb movements in two basic volleyball techniques, namely jump serve and spike. This research began from the importance of understanding biomechanics in improving performance while preventing shoulder and elbow injuries in university volleyball athletes. The research method used a quantitative descriptive approach with a high-speed video-based motion analysis technique (240 fps) analyzed using Kinovea software. The research sample consisted of 20 volleyball athletes from UKM UNDANA (10 male and 10 female) selected by purposive sampling. Parameters included joint angles, arm swing speed, and upper body segment momentum. The results showed that the optimal shoulder angle in the spike (165° ± 4.1) was greater than the jump serve (155° ± 3.6), with a higher arm swing speed in the spike (18.2 m/s ± 1.3) than the serve (14.5 m/s ± 1.1). The arm momentum value for the spike (7.8 kg·m/s ± 0.9) was also greater than the serve (6.2 kg·m/s ± 0.7). An independent t-test showed a significant difference (p < 0.05) in these three parameters. In conclusion, the spike exerted greater shoulder tension, a more explosive swing speed, and greater momentum than the jump serve. These results suggest that coaches should design exercises that synchronize movement and strengthen the shoulder muscles.